The relationship between environmental performance and firm value: the moderating role of board gender diversity : Evidence from Nordic companies - Takanen, Emmi (My University, 2025)
Corporate Social Responsibility (CSR) has attracted significant attention during the recent years, both in academic research and among businesses and their stakeholders. Additionally, Environmental, Social, and Governance (ESG) factors are continuously being integrated into companies core business actions and implemented into companies strategies. As the importance of ESG initiatives grows, this has led to the need of different regulations being needed to monitor these initiatives, as ESG initiatives are no longer completely voluntary for companies. Thus, for instance the European Union has taken a leading role when it comes to sustainability and has continuously worked to maintain the progress of ESG initiatives and disclosure of these. Recently, the European Union has increased regulation related to companies disclosure of ESG initiatives called the Corporate Sustainability Reporting Directive, which requires companies in the EU to disclose their ESG matters as part of their annual reports. The effect of ESG performance on firm value measured by Tobin’s Q has been historically studied among academic literature, focusing only on the environmental performance and its relationship to firm value has been fewer. Former studies have found conflicting results from researching ESG performance and firm value, thus it has been suggested that it could be more beneficial to focus the research on only one of the dimension, as it could give more extensive results to the subject and give more insight. Prior research on the subject of analyzing the matter of environmental performance and firm value are fewer in the Nordic region. Nordic region has been identified as an interesting region to conduct research on ESG performance and firm value, as the culture among Nordic countries demands a strong transparency between companies and its stakeholders. Hence, it has gained interest on researching whether the relationship in this kind of region might give different results. As the market demands and needs continuously keep evolving, companies are demanded to consider not only the value generation of the company but also the expectations of the stakeholders. Thus, the subject of board gender diversity has emerged in academic research. Prior research has indicated that having more gender diversity on the boards of companies might lead more comprehensive decision-making and decisions that take sustainability factors more into consideration. Thus, the growing need from stakeholders for firms to implement processes and strategies that take social responsibility into account, has resulted in the emergence of the subject of board gender diversity.

Lähivuosien aikana yritysvastuu on herättänyt merkittävää kiinnostusta niin tieteellisissä tutkimuksissa kuin yrityksissä ja niiden sidosryhmissä. Lisäksi ympäristöön, yhteiskuntaan ja hyvään hallintotapaan (ESG) liittyvät tekijät ovat yhä tiiviimmin osa yritysten ydinliiketoimintaa ja strategioita. ESG-aloitteiden merkityksen kasvaessa on syntynyt tarve sääntelylle, jolla näitä aloitteita voidaan valvoa, sillä ESG-toimet eivät enää ole yrityksille täysin vapaaehtoisia. Euroopan unioni on ollut edelläkävijä kestävän kehityksen saralla ja pyrkinyt jatkuvasti edistämään ESG-aloitteita ja niiden raportointia. Viime aikoina EU on kiristänyt sääntelyä, joka koskee yritysten ESG-raporttien julkistamista. Uuden yritysvastuudirektiivin (Corporate Sustainability Reporting Directive) myötä EU:ssa toimivien yritysten on sisällytettävä ESG-asiat osaksi tilinpäätöksiään. Vaikka ESG-suorituskyvyn vaikutusta yrityksen arvoon (mitattuna Tobinin Q:lla) on aiemmin tutkittu laajasti tieteellisissä tutkimuksissa, ympäristöllisen suorituskyvyn ja sen yhteyteen yrityksen arvoon on keskitytty huomattavasti vähemmän. Aiemmat tieteelliset tutkimukset ovat havainneet ristiriitaisia tuloksia ESG-suorituskyvyn ja yrityksen arvon välisestä suhteesta. Tämän vuoksi, tieteellisissä tutkimuksissa on herännyt kysymys siitä, voisiko tutkimuksen kohdentaminen vain yhteen ESG:n ulottuvuuteen tuottaa merkityksellisempää tietoa aiheesta. Aiempia tutkimuksia ympäristöllisen suorituskyvyn ja yrityksen arvon välisestä yhteydestä on Pohjoismaisessa kontekstissa tehty ainoastaan muutamia. Pohjoismaita pidetään kuitenkin kiinnostavana alueena tutkia ESG suorituskyvyn ja yrityksen arvon välistä suhdetta, sillä pohjoismainen kulttuuri korostaa vahvaa avoimuutta yritysten ja niiden sidosryhmien välillä. Tämän vuoksi lähivuosina kiinnostus on herännyt siitä, mikäli tällainen toimintaympäristö voisi antaa aiheen tutkimukselle eriäviä tuloksia. Markkinoiden jatkuvasti kasvavat vaatimukset ja tarpeet kehittyvät kehittymistään ja yrityksiltä edellytetään nykyään arvon tuottamisen lisäksi myös sidosryhmien odotusten huomioon ottamista. Tämän seurauksena yritysten hallitusten sukupuolten monimuotoisuus on noussut akateemisen tutkimuksen kohteeksi. Aiemmat tutkimukset ovat osoittaneet, että sukupuolten monimuotoisuus yritysten hallituksissa saattaa johtaa kokonaisvaltaisempaan päätöksentekoon sekä päätöksiin, joissa kestävyyteen liittyvät tekijät otetaan paremmin huomioon. Sidosryhmien kasvavat odotukset yhteiskuntavastuullisesta toiminnasta ovatkin osaltaan nostaneet esiin hallitusten sukupuolten monimuotoisuuden merkityksen.
Keywords: vastuullinen sijoittaminen; ekotehokkuus; yrityksen arvonmääritys; executive boards; environmental responsibility; corporate responsibility; environmental reporting; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Laskentatoimen ja tilintarkastuksen maisteriohjelma|en=Master's Programme in Accounting and Auditing|